AN UNUSUAL ANOMALY OF THE SUPERIOR EXTREMITIES IN A TARASCAN INDIAN GIRL - EVANS, DG; ALFARO, SK; ALFARO, A (WAYNE UNIVERSITY, DETROIT, EUA, 1950)
Rickettsiae were found in the blood of 31 out of 47 mice (659%) and of 19 out of 92 rats (206%) infected intranasally with rickettsiae of murine type They were present in the blood of all 24 mice infected in the same way with rickettsiae of classic typ
ANAT REC
Keywords: UNUSUAL, ANOMALY, SUPERIOR- EXTREMITIES, TARASCAN, INDIAN; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOGIA CLINICA